Multilevel Spinal Injury: Incidence, Distribution and Neurological Patterns - Khadka, Yagya; Lakhey, Rajesh B; Kafle, Dinesh (Journal of Institute of Medicine Nepal, 2020)
Introduction Fractures and dislocation of spine are serious injuries that most commonly occur in young people. Spinal injury at more than one level is not uncommon. Awareness of multilevel injury of the spine and associated neurological patterns is important for the proper initial management of the patient.MethodsThis was a prospective observational study carried out in Department of Orthopedics, Maharajgunj Medical Campus, Institute of Medicine, Tribhuvan University, Kathmandu, Nepal from February 2012 to September 2013. Sixty cases of age group between 18 to 63 years of traumatic spinal injury were enrolled. Patients were examined clinically and radiographically.ResultsOut of 60 patients, multilevel spinal injury occurred in 26 (43.3%) patients; 10 (16.67%) had contiguous spinal injury and 16 (26.67%) had non-contiguous spinal injury. There were 5 type A pattern spinal injury. Contiguous spinal injury most commonly occurred at level L1/L2 (n=4, 40%) and most had Frankel grade E neurology (n=6, 60%) followed by Frankel grade D (n=2, 20%). Non-contiguous lesions most commonly occurred at thoracic spine and had Frankel grade E neurology in most cases (n=10, 16.67%) followed by grade B and C (n= 2, 2.33% each).ConclusionMultiple spinal injury was a common pattern of injury, which occurred in 26 (43.3%) patients out of 60 patients enrolled in our study. Multilevel spinal injury is common. We should be aware about its occurrence. We should evaluate for multilevel spinal injuries, so as not to miss them, especialy non-contiguous injuries, in the patients presenting with spinal injury.